Risk factors for postoperative pancreatic fistula: Analysis of 539 successive cases of pancreaticoduodenectomy - Hu, Bing-Yang; Wan, Tao; Zhang, Wen-Zhi; Dong, Jia-Hong (World journal of gastroenterology : WJG, 2016)
AIM To analyze the risk factors for pancreatic fistula after pancreaticoduodenectomy.METHODS We conducted a retrospective analysis of 539 successive cases of pancreaticoduodenectomy performed at our hospital from March 2012 to October 2015. Pancreatic fistula was diagnosed in strict accordance with the definition of pancreatic fistula from the International Study Group on Pancreatic Fistula. The risk factors for pancreatic fistula were analyzed by univariate analysis and multivariate logistic regression analysis.RESULTS A total of 269(49.9%) cases of pancreatic fistula occurred after pancreaticoduodenectomy,including 71(13.17%) cases of grade A pancreatic fistula,178(33.02%) cases of grade B,and 20(3.71%) cases of grade C. Univariate analysis showed no significant correlation between postoperative pancreatic fistula(POPF) and the following factors: age,hypertension,alcohol consumption,smoking,history of upper abdominal surgery,preoperative jaundice management,preoperative bilirubin,preoperative albumin,pancreatic duct drainage,intraoperative blood loss,operative time,intraoperative blood transfusion,Braun anastomosis,and pancreaticoduodenectomy(with or without pylorus preservation). Conversely,a significant correlation was observed between POPF and the following factors: gender(male vs female: 54.23% vs 42.35%,P = 0.008),diabetes(non-diabetic vs diabetic: 51.61% vs 39.19%,P = 0.047),body mass index(BMI)(≤ 25 vs > 25: 46.94% vs 57.82%,P = 0.024),blood glucose level(≤ 6.0 mmol/L vs > 6.0 mmol/L: 54.75% vs 41.14%,P = 0.002),pancreaticojejunal anastomosis technique(pancreatic duct-jejunum double-layer mucosa-to-mucosa pancreaticojejunal anastomosis vs pancreatic-jejunum single-layer mucosa-tomucosa anastomosis: 57.54% vs 35.46%,P = 0.000),diameter of the pancreatic duct(≤ 3 mm vs > 3 mm: 57.81% vs 38.36%,P = 0.000),and pancreatic texture(soft vs hard: 56.72% vs 29.93%,P = 0.000). Multivariate logistic regression analysis showed that gender(male),BMI > 25,pancreatic duct-jejunum double-layer mucosa-to-mucosa pancreaticojejunal anastomosis,pancreatic duct diameter ≤ 3 mm,and soft pancreas were risk factors for pancreatic fistula after pancreaticoduodenectomy.CONCLUSION Gender(male),BMI > 25,pancreatic duct-jejunum double-layer mucosa-to-mucosa pancreaticojejunal anastomosis,pancreatic duct diameter ≤ 3 mm,and soft pancreas were risk factors for pancreatic fistula after pancreaticoduodenectomy.